SPE Annual Technical Conference and Exhibition 1995
DOI: 10.2118/30523-ms
|View full text |Cite
|
Sign up to set email alerts
|

An MWD Downhole Assistant Driller

Abstract: Identification of drilling problems is most commonly achieved by simple comparisons of surface and downhole time-averaged measurements of weight and torque, or by shock and vibration sensors located either downhole or at the surface. Various drilling phenomena are more complex than can be described by these simple shock and vibration measurements. The interpretation of drilling vibration data collected at the surface requires specialized expertise, and can be difficult. Sometimes downhole phenomena are not int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Understanding these detrimental phenomena and finding ways to avoid them can be the first step towards achieving high quality LWD acoustic, especially quadrupole, measurements. Gravem et al 8 , Hutchinson et al 9 , and Dubinsky et al 10 have demonstrated how an integrated approach utilizing a closedloop drilling control system can drastically improve drilling dynamic conditions downhole and, in turn, the quality of all LWD formation evaluation measurements including acoustics.…”
Section: Drilling Dynamics and Quadrupole Measurementsmentioning
confidence: 99%
“…Understanding these detrimental phenomena and finding ways to avoid them can be the first step towards achieving high quality LWD acoustic, especially quadrupole, measurements. Gravem et al 8 , Hutchinson et al 9 , and Dubinsky et al 10 have demonstrated how an integrated approach utilizing a closedloop drilling control system can drastically improve drilling dynamic conditions downhole and, in turn, the quality of all LWD formation evaluation measurements including acoustics.…”
Section: Drilling Dynamics and Quadrupole Measurementsmentioning
confidence: 99%
“…Traditional well diameter of kick off section is relatively small [3,4], and the downhole monitoring and control tools have been used successfully [5,6]. So the use of mature technologies is clearly a good choice.…”
Section: Introductionmentioning
confidence: 99%
“…Drillstring guided waves contain information about drilling conditions (MacPherson et al, 1993;Hutchinson et al, 1995) and can be used to transmit data from the bit location to the surface. For instance, Rector and Marion (1991) and Miranda et al (1996) investigate the potentials of the extensional waves traveling through the drillstring for while-drilling prediction ahead of the bit.…”
Section: Introductionmentioning
confidence: 99%